Transformasi Akulturasi Islam dalam Tradisi Grebeg Suro Desa Sumbermujur, Kabupaten Lumajang - Yaqqin, Ahmad Tataq Haqqul; Pratiwi, Linda (Local History & Heritage, 2025)
This study examines the transformation of Islamic acculturation within the Grebeg Suro tradition in Sumbermujur Village. Grebeg Suro represents a fusion of Javanese cultural elements and Islamic teachings, illustrating the dynamic interplay between local beliefs and Islam. As a socio-cultural phenomenon, this tradition reflects how Islamic values engage in dialogue with indigenous customs to form a distinctive communal practice. The research aims to explore the procession of the Grebeg Suro tradition and analyze the manifestations of Islamic acculturation within it. Employing the historical method, this study reveals that the Grebeg Suro celebration in Sumbermujur Village embodies a synthesis of Islamic and local traditions, as reflected in its ritualistic proceedings. The findings highlight the adaptability of Islam in negotiating with local cultural frameworks to shape a unique religious and cultural identity. This study contributes to a deeper understanding of how religious traditions evolve through cultural interaction and adaptation.